Assessment of the magnitude and contributing factors of expired medicines in the public pharmaceutical supply chains of Western Ethiopia - Gamachu Diriba; Gemmechu Hasen; Yesuneh Tefera; Sultan Suleman (BMC Health Services Research, 2023)
Abstract Background The magnitude of expired medicines in supply chains are increasing globally due to lack of strict control of the supply chain, poor storage management and oversupply of medicines. This situation is very serious in resource-poor countries, including Ethiopia, where the supply of medicines is limited. Therefore, this study aimed to assess the magnitude and the contributing factors of expired medicines in the Public Pharmaceutical Supply Chains of Western Ethiopia. Methods Explanatory sequential study design involving mixed quantitative and qualitative approach were employed among 62 public pharmaceutical supply chains of Western Ethiopia from July1 to August 30, 2021. An observational checklist and the self-administered questionnaire were used to review all records of the expired medicine file and to abstract secondary data on the extent, types of expired medicines and its contributing factors. The collected data was cleared, filtered, and coded using Microsoft Excel® 2010, and exported to SPSS version-23 (Amsterdam, Netherland) for statistical analysis. Bivariate logistic regression was used to check association between the outcome and independent variables. Multivariate logistic regression was analyzed when p-value is less than or equal to 0.25 in bivariate binary logistic regression, considering the statistical at p-value < 0.05. Moreover, audio recordings were transcribed and coded for emergent themes using thematic analysis. Results The study revealed 5% expire rate over past two financial (2012 up to 2013) years and the total amount of expired drugs is estimated at 20 million Ethiopian Birr (ETB). Tetanus antitoxin (TAT), in terms of single drug value, had the highest drug expiry (4,110,426.43ETB: 20%), followed by liquid dosage forms (11,614,266.11 ETB: 57%). The Binary logistic regression result indicated that, poor store management were more likely associated with the magnitude of expired medicine than those with good store management (COR: 10.706, 95% CI: 2.148, 53.348). Multivariate logistic regression revealed that poor store management (AOR: 9.718, 95% CI: 1.474, 64.082) was a significant contributor to the expire rate at 5% (P < 0.05). Most facilities did not have a procedure, and programme for disposing of expired medicines. According to key informants, inadequate inventory management, lack of policy and implementation of standards are the main contributing factors of the medicine's expiration. Conclusion and recommendations The current study found that the overall rate of medication expiration is high, at a significant cost to the budget. Inadequate inventory management, lack of policy, and implementation of standards are the main contributing factors to the medicine's expiration, as cited by key informants. Further research is necessary to determine the quality and efficacy of these expired drugs to extend their shelf life to ensure adequate access to drugs in resource-limited settings.